CANCER REGISTRATION IN RSUP DR.SARDJITO - Savitri Citra Budi, Vitri (PORMIKI & IFHIMA, 2014)
Background: Cancer Register is required to overcome the increase in the number of deaths from the disease of cancer patients as well as help perform the prevention, early detection, diagnosis, therapy, rehabilitation and treatment of terminal cancer disease. According to Johns (2002) cancer register can be used to collect information in the long period required to establish the diagnosis and handling of cancer patients. Results of this study can provide improvement suggestions for the creation of system management data recording quality in cancer patients at Tulip Cancer Installation, Dr. Sardjito Hospital Yogyakarta. Methods: This study was a descriptive case study approach. Data collection techniques used observation, interviews and document studies. The validity of research data by triangulation method. Result: The system of recording data in cancer patients Tulip Cancer installation look in the medical records and cancer registers. Cancer registration using a computer application called SRIKANDI (Sistem Registrasi Pasien Kanker di Indonesia). Implementation of data collection with SRIKANDI not to run in real-time. Results of item analysis on the cancer register was found 100% of the data on the follow-up was not filled. Data recording system constraints cancer patients and procedures contained in the source data.